Sister Robots - food and medicine carriers - Gurung, Bikash; Singh, Anil; Japrel, Pankaj; Joshi, Rishan; Chaudhary, Prithvi (Applied Science and Technology Annals, 2020)
Sister Robots - ‘Food and Medicine Carrier Robot’ are manually controlled robots which can be used in Corona Testing Hospital where health representatives or medical professionals need to carry food and medicine from the kitchen of the hospital to the patient isolation room. Robotics Association of Nepal [RAN] along with Team Robonauts, Team Kantibir and Team Oztec have developed the different versions of Sister Robots. The first version of the Robot - Sister V.1 is now working at the provincial hospital of Province no. 3, Hetauda Hospital. The Robot was built in support of Nepal Engineers’ Association [NEA] and handed over to Honorable Chief Minister, Province No.3 Dormani Poudel. Sister V.1 can help frontline health professionals communicate with COVID-19 suspected/infected patients in the isolation room, deliver essential foods and medicines as well. Sister V.1 took 20 days for its completion. The development team further developed second version of Sister Robot [Sister V.2]. First piece of Sister V.2 has been completed and 5 more are on the verge of development. Armed Police Force [APF] Hospital has made a trial of Sister V.2. Sister V.2 has been upgraded with a double 12V 8000MAH battery system for higher power performance, dual FPV camera system for Top 90 degree rotation back view and Front 180 degree bottom view. Food and Medicine can be easily delivered and COVID-19 can sanitize their hands with automatic sanitizer as well. Phase 1 product development has been completed and Phase 2 small scale production is currently running. The phases are defined based on the upgrade of the Robots as the team believes in iteration of the robot and customization as well. Mass scale production of Sister Robots on phase 3 Version 3 [Sister V.3] will consist of different lines of Robots with different specifications. More cost effective technologies will be introduced and automation will be a priority of Robot development. Research Center for Applied Science and Technology (RECAST) and Sagarmatha Engineering College collaborated with RAN for 6 more robots to develop financially. Phase 3 focuses in bringing Sister V.3 at each and every hospital in Nepal through collaborative partnerships and safety campaigns.